Pengaruh manajemen laba terhadap efisiensi investasi dengan Good Corporate Governance sebagai variabel moderasi - Alesiya Nur Asita; wahyu pramesti (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2023)
This study aims to determine the effect of earnings management on investment efficiency with good corporate governance as a moderating variable. The population in this study was conducted on manufacturing companies listed on the Indonesian stock exchange in 2017-2021. The type of research used is quantitative. The sampling technique used purposive sampling so that a sample of 100 companies was obtained and the number of observations was 500 observational data. The data analysis technique is regression analysis and the data is processed using Eviews 10. The results showed that earnings management had a significant negative effect on investment efficiency and independent commissioners were able to moderate the effect of earnings management on investment efficiency while the size of the board of commissioners was not able to moderate the effect of earnings management on investment efficiency.